Utilization of reproducing kernel hilbert space method on the survival data of leukemia patients - Abdul Manaf, N.; Ibragimov, Gafurjan; Abu Bakar, Mohd Rizam (Centre for Environment, Social and Economic Research Publications, 2015)
The theory of reproducing kernel has been recognized as a useful instrument in several areas of mathematical research. This has been verified by researches done by Aronszajn (1950), Berlinet et al. (2003), Burbea (1976), Hille (1972), Li et al. and Wahba (1998), (2003). Many statistical problems can also be solved using models related to reproducing kernel Hilbert space (RKHS).